2015
DOI: 10.1080/02640414.2015.1112022
|View full text |Cite
|
Sign up to set email alerts
|

The health-enhancing efficacy of Zumba® fitness: An 8-week randomised controlled study

Abstract: Telephone number (44) 75 5132 1637 Co-author email addressesHannah J. Moir, E-mail: h.moir@kingston.ac.uk; Elizabeth Pummell, E-mail: e.pummell@kingston.ac.uk; Allan Knox, E-mail: allan.knox@uws.ac.uk; Chris Easton, E-mail: chris.easton@uws.ac.uk Acknowledgement and disclosure statementThe authors wish to thank all the participants who volunteered their time for this project and in doing so made the completion of this research possible. No financial support was sought. No conflicts of interest are declared. Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(76 citation statements)
references
References 32 publications
7
59
0
2
Order By: Relevance
“…Main findings from this study indicated that the Zumba intervention led to significant reduction in weight and BMI as well as an increase in flexibility. This finding is consistent with other studies, where a Zumba dance program showed similar positive effects in comparable populations [45,46,49,50]. Specifically, research indicated that following a 16-week intervention, diabetic patients in intervention group gained higher aerobic capacity, flexibility, and intrinsic motivation, in addition to reduction in weight, BMI, and waist circumference [50].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Main findings from this study indicated that the Zumba intervention led to significant reduction in weight and BMI as well as an increase in flexibility. This finding is consistent with other studies, where a Zumba dance program showed similar positive effects in comparable populations [45,46,49,50]. Specifically, research indicated that following a 16-week intervention, diabetic patients in intervention group gained higher aerobic capacity, flexibility, and intrinsic motivation, in addition to reduction in weight, BMI, and waist circumference [50].…”
Section: Discussionsupporting
confidence: 91%
“…Zumba is an aerobic fitness program which combines Latin and other international upbeat music with dance moves and can enhance aerobic fitness [43]. A few intervention studies have examined the effectiveness of Zumba on health and physical fitness outcomes among multiple clinical and non-clinical populations [11,44,45,46,47]. A systematic review conducted on the overall health benefits of Zumba reported that it enhanced aerobic and cardiovascular outcomes such as weight loss (1-3.6% reduction), body mass index (BMI) (1.1-3.7%), and waist circumference (3.5-4%) in participants within programs that lasted 8-40 weeks [47].…”
Section: Discussionmentioning
confidence: 99%
“…Babayigit et al (2014) indicate that weight loss program with a step dance and aerobic dance are as useful tools as the other sports which enable to decrease body fat percentage, in improving weight for university students. The Zumba fitness program was designed to improve the cardiovascular risk factors of the Zumba fitness program for overweight non-exercise women in the study of health benefits (Domene et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous physiological and psychological benefits of Zumba ® have been identified in healthy populations, including improvements in dynamic balance, quality of life, lower pain perception, less interference with daily activities, higher self-perception of physical strength, and greater autonomy and purpose in life. [27][28][29][30] Since many of these aspects are affected in PD, it can be hypothesized that Zumba ® could benefit this population. However, to date there is no study on this type of exercise in neurological populations.…”
Section: Introductionmentioning
confidence: 99%